TREE PRESERVATION ORDER (ACT 172) ADOPTION PROCESS WITHIN THE NATIONAL DEVELOPMENT PLANNING FRAMEWORK - Nik Mohamed Sukri, Nik Adlin; Ismail, Zulhabri; Wan Ariffin, Wan Tarmeze; Mohd Nordin, Rumaizah (PLANNING MALAYSIA, 2020)
This study was conducted to obtain comprehensive information on the process of Tree Preservation Order or TPO (Act 172) adoption by the states in the context of National Development Planning Framework (NDPF) that includes the formulation and adoption of TPO Rules. The study was part of the authors’ research in finding answers to the lack of TPO (Act 172) implementation in the country. The data were acquired through consultation with PLANMalaysia and state JPBDs, and by reviewing the agencies’ documents. The results, presented in the form of process flowcharts, would be useful for the current and future research in making evaluation concerning the adequacy of planning and actions taken during the adoption process that would ensure TPO (Act 172) implementation. This study preliminarily concludes that the planning and actions taken were adequate, i.e., done in an orderly manner and followed the procedures common to the NDPF. However, the next step in ensuring that the TPO (Act 172) adoption is effective, TPO (Act 172) implementation must be put as high priority in the work plans of each related agency.